Age and growth comparisons of Hovsgol grayling (Thymallus nigrescens Dorogostaisky, 1923), Baikal grayling (T. baicalensis Dybowski, 1874), and lenok (Brachymystax lenok Pallas, 1773) in lentic and lotic habitats of Northern Mongolia. (17th January 2017) - Tsogtsaikhan, P.; Mendsaikhan, B.; Jargalmaa, G.; Ganzorig, B.; Weidel, B. C.; Filosa, C. M.; Free, C. M.; Young, T.; Jensen, O. P.
Summary: Despite concern over the conservation status of many Mongolian salmonids and the importance of their ecological role in Mongolia's aquatic ecosystems, little is known about their basic biology. Hovsgol grayling ( Thymallus nigrescens ) is endemic to Lake Hovsgol, Mongolia and listed as endangered on the Mongolian Red List. Baikal grayling ( T. baicalensis ) and lenok ( Brachymystax lenok ) are found in lakes and rivers throughout the Selenge drainage. A detailed study of the age and growth of these three salmonids was conducted based on 1, 682 samples collected from July 2006 to July 2013 in Lake Hovsgol, its outlet the Eg River, and one of the Eg's largest tributaries, the Uur River. Our results suggest that Hovsgol grayling in particular can reach a much older maximum age (17 years in our samples) than previously believed based on aging from scales. Female Hovsgol grayling were heavier at a given length than their male counterparts. Lenok had a greater average length‐at‐age in Lake Hovsgol compared to the rivers and greater weight‐at‐length in the warmer Uur River than in the Eg; female lenok from the rivers had a greater average length‐at‐age than their male counterparts. This study provides critical new information for the management and conservation of these threatened salmonid species in Mongolia.